What is a Philosophical Institution? Or: Address, Transmission, Inscription - Badiou, Alain (Cosmos and History: The Journal of Natural and Social Philosophy, 2006)
This translation is taken from Alain Badiou, emConditions/em, Paris: Eacute;ditions du Seuil, 1992, pp.83-90. Except for some final improvements, this is the text was first presented, in 1989, as a colloquium intervention at the Collegrave international de philosophie.